State Control by Stealth in the Big Data Era – From WeChat to the Social Credit System in China - Li, Grace (Journal of Telecommunications and the Digital Economy, 2021)
This paper begins with a brief study on the development of the Chinese all-in-one app, WeChat, explaining how WeChat secured its popularity as the multi-functional ubiquitous mobile app in China. By using WeChat as an example, this paper further studies how the Social Credit System (SCS) in China was established out of collaboration between the Chinese government and eight entrusted private companies. This paper then analyses and evaluates the SCS from a socio-legal perspective, focusing on two key implications: the opaque algorithms and the potential abuse of power. The paper argues that the SCS needs to first gain trust from Chinese citizens. A starting point would be immediate action to standardise and reduce the opacity of the prototype. To enhance the longevity and effectiveness of the SCS, developing a legal framework to prohibit potential information misuse by the State and the entrusted companies is crucial: it needs to be put in place sooner rather than later. In constructing the much-needed legal framework, developing privacy laws is certainly a core step, but the framework needs more than just privacy laws. One crucial safeguard is the requirement for an independent tribunal or ombudsman to deal with credit-related complaints fairly and efficiently.